ANALISIS RENCANA PELAKSANAAN PEMBELAJARAN (RPP) BIOLOGI SISWA KELAS VIII SEMESTER I DI SMP NEGERI 1 LEMBAH MELINTANG KABUPATEN PASAMAN BARAT - Aufa, Anna Linda (Pendidikan Biologi, 2014)
This research background was based on some problem. Firstly, the results of the eight grade studentsâ biology test at first semester were low. Secondly, the teacherâs ability is still less in constructing the appropriate indicator with the students characteristic and school condition. Thirdly, the lesson plan that was made by the biologyâs teacher did not match with the standard of IPKG I, but it was written together with the other teacher. Fourthly, some teacher thought that the lesson plan was only made to complete the teacherâs functional task for the evaluation of DP3, so, the lesson plan did not apply well in the teaching and learning process by the teacher. Fifthly, the learning process will be achieved if the teacher could master the methods, strategies and approaches which is suitable with the situation and condition that happen toward the students while learning activity. And it is manually used and applied in the teaching and learning process. This research was aimed to analyze the biology lesson plan at eight grade students of SMPN 1 LembahMelintang, West Pasaman. This research was categorized to the descriptive research design. The population was taken from the biologyâs lesson plans at eight grades students in the first semester. The lesson plan was made by two biologyâs teachers in the SMPN 1 LembahMelintang, West Pasaman. The sample of this research used the total sampling technique that was the lesson plans which had been constructed by the biologyâs teachers in the first semester of SMPN 1 LembahMelintang, West Pasaman in the academic years of 2013/2014. The instrumentation used the questionnaire based on IPKG 1which had been developed by Mulyati, et al (2013). The final result of this research described that the completeness of the lesson plan components on the prior component is 80, 5 %, meanwhile on the incompleteness component is 19, 5 %, and then from the result of the lesson plan evaluation is 65, 01%. Based on the result, the researcher conclude that the lesson plan of SMPN 1 LembahMelintang, West Pasaman at eight grade students in the first semester have an enough standard criterion.